Parodontoprotective action of oral applications of soy isoflavons in rats after orthodontic operation on the background of experimental diabetes mellitus - Mohammed Ali Mehrdad Azari; A. L. Morozov (Kazimierz Wielki University, 2019)
Background.  To determine the periodontoprotective effect of soy isoflavones in rats after orthodontic surgery on the background of diabetes mellitus. Methods. In rats, type 1 diabetes was reproduced with aloxane (intraperitoneally at a dose of 100 mg / kg once). From day 12, rats were fitted with orthodontic springs. One of these groups of rats received oral gel applications with soy isoflavones from the first day of the experiment at a dose of 0.5 ml daily for 34 days. The activity of elastase, catalase, urease, lysozyme and the content of malondialdehyde (MDA) were determined in the gum. In the alveolar process of the lower jaw, the activity of alkaline (alkaline phosphatase) and acid (APH) phosphatases, the content of calcium and protein were determined. The antioxidant-prooxidant index (API) was calculated by the ratio of catalase activity and MDA content, the degree of dysbiosis was calculated by the ratio of the relative activities of urease and lysozyme, the mineralizing index (MI) was calculated by the ratio of alkaline phosphatase and APH activity, and the degree of mineralization (DM) was calculated by the ratio of calcium and protein. Results. In rats with diabetes mellitus, the level of elastase, MDA, urease and the degree of dysbiosis increased with a decrease in the API index and lysozyme activity. Orthodontic surgery showed a certain tendency to normalize these parameters, while the application of a gel containing soy isoflavones completely normalized all indicators. In the bone tissue of periodontium in rats with diabetes mellitus, the activity of alkaline phosphatase and MI decreased, but the activity of APH increased. Orthodontic surgery significantly increased the activity of alkaline phosphatase, slightly changing the activity of APH and the index of API. Application of the gel with isoflavones completely normalized the activity of phosphatases, MI and significantly increased the degree of mineralization of bone tissue. Conclusion. Rats with type 1 diabetes develop periodontitis. Orthodontic surgery does not exacerbate the pathological condition, showing even a slight tendency to normalize. Oral applications of a gel containing soy isoflavones have a periodontoprotective effect, normalizing all biochemical parameters of the gums and bone periodontal tissue.